Truth in hell and other essays on politics and culture, 1935-1987. - Hans Speier; Arthur Vidich (Oxford University Press, 1989)
This collection of seminal essays spans the pioneer sociologist's entire career and survey five areas of thought: social theory, war and militarism, public opinion and progaganda, the history of literature, and ""the present and the future."" Reflecting the range of his concerns and his experience as a refugee from Nazi Germany, Speier's writings examine honor and social structure, hero worship, psychological warfare, and Shakespeare's King Lear among many other topics.